PENDAMPINGAN PEMBELAJARAN MAHARAH QIRAAH (MEMBACA TEKS AL-QURAN) PADA ANAK DI DESA PULO - Zainuri, Zainuri; nurjanah, siti (INAIFAS Press, 2025)
Abstract Arabic is one of the foreign languages ​​that is difficult to understand, digest, and comprehend by children. Sometimes the level of difficulty for a child in learning Arabic is at the reading level because Arabic lessons are very different both in terms of writing and how to read them. The purpose of this community service activity is to carry out a work program through mentoring children in Pulo Village in reading the Qur'an. The Qur'an is a guide to life that is always used by Muslims. In this community service research, the community service method is used. Researchers also collect data through observation and documentation based on primary and secondary sources. The results of the research activities that have been carried out can be concluded that this Qur'an reading mentoring program shows that learning the Qur'an using methods and stages is more effective in the results that have been achieved. This shows that motivation for children is also very much needed in the learning process to increase children's enthusiasm.